Antibody Avidity Maturation Following Recovery From Infection or the Booster Vaccination Grants Breadth of SARS-CoV-2 Neutralizing Capacity. (22nd December 2022) - Nakagama, Yu; Candray, Katherine; Kaku, Natsuko; Komase, Yuko; Rodriguez-Funes, Maria-Virginia; Dominguez, Rhina; Tsuchida, Tomoya; Kunishima, Hiroyuki; Nagai, Etsuko; Adachi, Eisuke; Ngoyi, Dieudonné Mumba; Yamasue, Mari; et al.
Abstract: Background: Cross-neutralizing capacity of antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants is important in mitigating (re-)exposures. Role of antibody maturation, the process whereby selection of higher affinity antibodies augments host immunity, to determine SARS-CoV-2 neutralizing capacity was investigated. Methods: Sera from SARS-CoV-2 convalescents at 2, 6, or 10 months postrecovery, and BNT162b2 vaccine recipients at 3 or 25 weeks postvaccination, were analyzed. Anti-spike IgG avidity was measured in urea-treated ELISAs. Neutralizing capacity was assessed by surrogate neutralization assays. Fold change between variant and wild-type neutralization inferred the breadth of neutralizing capacity. Results: Compared with early-convalescent, avidity indices of late-convalescent sera were significantly higher (median, 37.7 [interquartile range 28.4–45.1] vs 64.9 [57.5–71.5], P < .0001). Urea-resistant, high-avidity IgG best predicted neutralizing capacity (Spearman r = 0.49 vs 0.67 [wild-type]; 0.18–0.52 vs 0.48–0.83 [variants]). Higher-avidity convalescent sera better cross-neutralized SARS-CoV-2 variants ( P < .001 [Alpha]; P < .01 [Delta and Omicron]). Vaccinees only experienced meaningful avidity maturation following the booster dose, exhibiting rather limited cross-neutralizing capacity at week 25. Conclusions: Avidity maturation was progressive beyond acute recovery from infection, or became apparent after the booster vaccine dose, granting broader anti-SARS-CoV-2 neutralizing capacity. Understanding the maturation kinetics of the 2 building blocks of anti-SARS-CoV-2 humoral immunity is crucial. Abstract : Avidity maturation augments host immunity following a natural infection and/or vaccination. For protection against SARS-CoV-2, avidity maturation was progressive beyond acute recovery from infection or became apparent after the booster vaccine dose, and granted broader neutralizing capacity against variant strains.